(untitled) - Clifford F Gray (Boston, Massachusetts, 2000)
The book involves understanding the cause-effect relationships and interactions among the sociotechnical dimensions of projects. Technical issues of project management are thoroughly addressed, such issues are balanced and provided a context by a comprehensive of the human elements requiring consideration in the management of projects.
Keywords: industrial project management,risk management,time management